Influence of Indo-Pacific ocean currents on the distribution and demographic patterns of the brown seaweed Sargassum polycystum in tropical east Asia - Liang, Yanshuo; Zhang, Shuangshuang; Yan, Changxiang; Draisma, Stefano G. A.; Kantachumpoo, Attachai; Li, Zhao; Lin, Yude; Zhu, Jiang; Zhang, Jie; Duan, Delin (Frontiers in Marine Science, 2022)
Long-distance drifting of seaweeds driven by ocean currents is an ideal model for exploring population-level genetic connectivity and phylogeographic structure. In the Indo-Pacific convergence region, we integrated phylogeographic and ocean current data and Lagrangian particle simulations to explore how the ocean currents contributed to the biogeographical patterns and population genetic connectivity of Sargassum polycystum. The oceanographic transport and direction of gene flow was in line with contemporary ocean currents. The S. polycystum geographical dispersal from glacial refugia homogenized the footprint of genetic divergence. The multidisciplinary intersection provides insights into the evolutionary history and biogeographic conservation of tropical seaweeds in the Indo-Pacific convergence region.